1458. Epidemiology of Infectious Mononucleosis in Ambulatory Care Settings, United States, 2006–2019. (15th December 2022) - Chandra, Christina; Li, Jianheng; Dana Flanders, W; McPhee, Roderick; Paris, Robert; Buck, Philip; Chandramouli, Sumana; Hall, Susan; Lally, Cathy
Abstract: Background: Infectious mononucleosis (IM) is a contagious illness most frequently caused by Epstein-Barr virus (EBV). There are no recent published studies characterizing the burden of IM in the general US population over time. Methods: Nationally representative samples of US ambulatory medical care data were utilized to estimate the N and proportion of visits with an IM diagnosis (based on ICD-9/10 codes) by time period. The National Ambulatory Medical Care Survey (NAMCS: 2006–2015) and National Hospital Ambulatory Care Survey (NHAMCS: 2006–2019) allow estimation of annual visits in free-standing and hospital-based ambulatory care, including emergency departments (EDs). Restricted cubic spline models were implemented to assess temporal trends. NHAMCS data were divided based on availability: combined outpatient and ED (2006–2011) and ED-only (2012–2019). Analyses were conducted using SAS 9.4 & SUDAAN 11.0.3. Results: There were 3, 182, 082 IM-related visits in NAMCS, 599, 837 in combined outpatient and ED NHAMCS, and 449, 000 in ED-only NHAMCS across study years. For overlapping study years, 2006–2011, across all databases the average annual number of IM-related visits was 419, 927. Persons aged 10–30 years comprised the majority of IM-related visits: 61% in NAMCS, 88% in combined NHAMCS, and 85% in ED-only NHAMCS. While 66% of IM visits were made by females in NAMCS, this proportion was lower in combined NHAMCS (58%) and ED-only NHAMCS (51%). Most IM-related visits were among non-Hispanic white patients: 92% in NAMCS, 87% in combined NHAMCS, and 67% in ED-only NHAMCS. Across databases and years, there were no consistent linear trends in IM-related visits (Figure 1). Rates of IM-related visits in NAMCS decreased from 4.18 (95% confidence interval [CI]: 3.02–5.78) in 2006–2009 to 2.89 (95% CI: 1.40–5.96) per 10, 000 visits in 2013–2015; decreased from 4.94 (95% CI: 3.41, 7.16) in 2006–2007 to 3.56 (95% CI: 2.33–5.45) per 10, 000 visits in 2010–2011 in combined NHAMCS data; and increased from 3.61 (95% CI: 2.30–5.67) in 2012–2014 to 5.98 (95% CI: 3.20–11.17) per 10, 000 visits in 2018–2019 in ED-only data. Conclusion: This study contributes epidemiologic information concerning IM and EBV by estimating US ambulatory medical care burden of IM over time and describing the demographics of those affected. Disclosures: Christina Chandra, MPH, Moderna, Inc.: Contractor Jianheng Li, MBBS, MPH, Moderna, Inc.: Contractor W. Dana Flanders, MD, DSc, MPH, MA, Moderna, Inc.: Contractor Roderick McPhee, MD, PhD, Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Robert Paris, MD, Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Philip Buck, PhD, MPH, Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Sumana Chandramouli, PhD, Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Susan Hall, PhD, MS, Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Cathy Lally, MSPH, Moderna, Inc.: Contractor.